Metode, Sistem dan Prinsip Pembelajaran Bahasa Arab yang Inovatif - M. Asy'ari (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2019)
Arabic is the second language used in Indonesia. Therefore, the good and appropriate methods, systems and principles of learning may certainly contribute to the achievement of the goals of Arabic language teaching and learning activities. When a teacher does not apply the methods, systems, and principles correctly, teaching will not be effectively directed. Today, there are many interactive and innovative Arabic learning models and techniques that can be applied by the teachers. The suitability of the application of methods, systems and principles will certainly increase the students’ passion in learning Arabic simultaneously and continuously. The author has conducted a study of the existence of methods, systems and principles of Arabic learning that are considered the most effective. This type of research was descriptive research in which the researcher described the mechanism of a process. The innovative Arabic learning system are, among others, integrated systems, separation systems, and combined systems. While, the principle of innovative Arabic language learning is the principle of priority, the principle of accuracy, the principle of gradation, the principle of motivation, and the principle of validation. In the end, by combining these aspects, the purpose of learning Arabic will be achieved perfectly.